A Structural Analysis of Host–Parasite Interactions in Achatina fulica (Giant African Snail) Infected with Angiostrongylus cantonensis - Eduardo J. Lopes-Torres; Raquel de Oliveira Simões; Ester M. Mota; Silvana Carvalho Thiengo (Pathogens, 2023)
Angiostrongylus cantonensis is a nematode parasite that resides in the pulmonary arteries of rodents, serving as its definitive hosts. The life cycle involves several species of non-marine gastropods as intermediate hosts, and the African giant snail Achatina fulica is considered one of the most important around the world. Experimental data concerning A. cantonensis infection in the African giant snail remains notably limited. This helminth causes eosinophilic meningitis or meningoencephalitis in humans, representing an emergent zoonosis in Brazil. Understanding the host–parasite relationship through the application of new tools is crucial, given the complex interaction between zoonosis and the intricate mechanisms involving wild/human hosts, parasite adaptation, and dispersion. The objective of this study was to employ SEM as a novel methodology to understand the structural organization of the host tissue, particularly the granuloma formation. This sheds light on the complex balance between A. fulica and A. cantonensis. Nine three-month-old snails were randomly selected and exposed for 24 h to a concentration of 2000 L1/dose of A. cantonensis. A necropsy was performed 37 days after the infection, and the samples were examined using light and scanning electron microscopy (SEM). The histopathological results revealed third-stage larvae of A. cantonensis associated with granulomas distributed throughout the head-foot mass, mantle, and kidney. Scanning electron microscopy of the histological section surface showed that the granuloma is surrounded by a cluster of spherical particles, which are distributed in the region bordering the larvae. This reveal details of the nematode structure, demonstrating how this methodology can enhance our understanding of the role of granulomas in molluscan tissue. The structural characteristics of granuloma formation in A. fulica suggest it as an excellent invertebrate host for A. cantonensis. This relationship appears to provide protection to the parasite against the host’s immune defense system while isolating the snail’s tissue from potential exposure to nematode antigens.